2015
DOI: 10.5194/gmdd-8-5235-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implementation of an optimal stomatal conductance model in the Australian Community Climate Earth Systems Simulator (ACCESS1.3b)

Abstract: Abstract. We implement a new stomatal conductance model, based on the optimality approach, within the Community Atmosphere Biosphere Land Exchange (CABLE) land surface model. Coupled land-atmosphere simulations are then performed using CABLE within the Australian Community Climate and Earth Systems Simulator (ACCESS) with prescribed sea surface temperatures. As in most land surface models, the default stomatal conductance scheme only accounts for differences in model parameters in relation to the photosyntheti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…1, when applied to biophysical models of photosynthesis and transpiration, closely matches the functional forms of empirical stomatal models, which themselves have extraordinary empirical support (2,5,7,27,34). For this reason, the WUEH is widely used to guard against out-of-sample behavior in the novel climates created in ecosystem models (35)(36)(37)(38)(39). Finally, several notable efforts have been made to extend WUEH to situations including soil moisture stress (11,12,28,33,(40)(41)(42) and competition (43) and to develop a theory of the value of λ over the short time scales during which it should be approximately constant and how λ should change over weeks, months, or seasons (9,11,12,28,32).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…1, when applied to biophysical models of photosynthesis and transpiration, closely matches the functional forms of empirical stomatal models, which themselves have extraordinary empirical support (2,5,7,27,34). For this reason, the WUEH is widely used to guard against out-of-sample behavior in the novel climates created in ecosystem models (35)(36)(37)(38)(39). Finally, several notable efforts have been made to extend WUEH to situations including soil moisture stress (11,12,28,33,(40)(41)(42) and competition (43) and to develop a theory of the value of λ over the short time scales during which it should be approximately constant and how λ should change over weeks, months, or seasons (9,11,12,28,32).…”
mentioning
confidence: 75%
“…In particular, knowledge of the large costs associated with low xylem potential, which was obtained after 1977, might have obviated the need for the assumption of a fixed water supply in CF77 (6). On the other hand, WUEH is widely applied where such costs are thought to be high, as in ecosystem models under climate change (35)(36)(37)(38)(39). We include all combinations of i-iii simply to explore the impact of each component on the predicted stomatal behavior and in recognition of the fact that Eq.…”
mentioning
confidence: 99%
“…It is also notable that ACCESS1‐0 and ACCESS1.3 occupy quite different branches on the dendrogram. Since a major difference between these models is the updated land surface scheme in ACCESS1.3 [ Bi et al ., ], this may imply that heat waves are sensitive to the way land surface processes are represented in these models, in agreement with the findings of previous studies [e.g., Kala et al ., ; Kala et al ., ]. However, it has been shown that differences in the atmospheric configurations between these models, in particular the simulation of clouds, may influence the seasonality of ENSO [ Rashid and Hirst , ] and therefore possibly the heat wave climatology.…”
Section: Resultsmentioning
confidence: 99%
“…2015a; Kala et al . ). Thus, performing all tests at both a daily and seasonal‐to‐yearly timescale is a relevant and crucial comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, WUE hypothesis has become the dominant hypothesis of stomatal regulation for 40 years (Ball et al 1987;Medlyn et al 2011Medlyn et al , 2013Lin et al 2015;Buckley 2017), and is widely thought to help avoid errors in predictions of climate models in future (i.e. out-of-training-sample) conditions (Bonan et al 2014;Kala et al 2015;Xu et al 2016).…”
Section: Introductionmentioning
confidence: 99%